2001
DOI: 10.1159/000046586
|View full text |Cite
|
Sign up to set email alerts
|

Update on Tumor Cell Procoagulant Factors

Abstract: Tumor cells produce tissue factor, cancer procoagulant, plasminogen activators and other factors that interact with the coagulation system, the fibrinolytic system and vascular or blood cells such that they can upset the normal homeostasis and balance between activation and inhibition of the coagulation and fibrinolytic systems. These activities play a role in tumor cell growth and metastasis, vascular wall function, and hemostasis. Proteases and their inhibitors are intimately involved in all aspects of the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
5

Year Published

2003
2003
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(55 citation statements)
references
References 52 publications
1
49
0
5
Order By: Relevance
“…The development of thrombi within vessels results from the disruption of the equilibrium between the prothrombotic and the antithrombotic factors that control clotting homeostasis; this imbalance may occur due to ongoing stimulus to thrombogenesis or a defect in the natural anti-coagulant or the fibrinolytic system. In cancer patients, several studies have reported high plasma concentrations of procoagulant proteins and decreased concentrations of functionally attenuated anti-coagulant factors [23][24][25]. Low fibrinolytic function has been also reported to be an important cause of vascular thrombosis in cancer patients [17].…”
Section: Discussionmentioning
confidence: 99%
“…The development of thrombi within vessels results from the disruption of the equilibrium between the prothrombotic and the antithrombotic factors that control clotting homeostasis; this imbalance may occur due to ongoing stimulus to thrombogenesis or a defect in the natural anti-coagulant or the fibrinolytic system. In cancer patients, several studies have reported high plasma concentrations of procoagulant proteins and decreased concentrations of functionally attenuated anti-coagulant factors [23][24][25]. Low fibrinolytic function has been also reported to be an important cause of vascular thrombosis in cancer patients [17].…”
Section: Discussionmentioning
confidence: 99%
“…(6)(7)(8) Tissue factor, the main activator of the coagulation cascade, forms a complex with factor VII in order to activate factors X and XI. The final pathway of this process is the transformation of prothrombin into thrombin.…”
Section: Procoagulant Factorsmentioning
confidence: 99%
“…A classic review of 182 cases of this "paraneoplastic" phenomenon emphasized the formation of venous and arterial platelet-rich microthrombi with secondary microangiopathic hemolytic anemia and a frequent association with mucin-rich adenocarcinomas (3). The term Trousseau syndrome is sometimes used more broadly to refer to any form of excessive coagulation associated with cancer (2,(4)(5)(6)(7)(8)(9)(10). The underlying pathophysiology is thought to be chronic subclinical disseminated intravascular coagulation caused by activated procoagulants.…”
Section: Introductionmentioning
confidence: 99%